2011
DOI: 10.1002/elps.201100250
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Endo H‐released serum N‐glycans using CE‐LIF and MALDI‐TOF‐MS – Application to rheumatoid arthritis

Abstract: High-mannose and hybrid-type N-glycans are present in human serum glycoproteins in low abundance but have recently been described to play an important role in immune responses. It is therefore important to find a strategy to selectively analyze their structures in the context of health and disease in order to understand their impact on disease mechanisms. We report here the characterization of high-mannose and hybrid-type N-glycans in total human serum. To this end, N-glycans were released using Endo-β-N-acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The changes in relative amount of neutral hybrid-type N-glycans H5N2 (m/z 1579.7) and H6N2 (m/z 1783.8) in 15 days adipogenically differentiated MSCs and undifferentiated MSCs were statistically significant. In addition, a glycan of the composition H10N1 was detected in trace amounts at m/z 2355.1, which was verified as the monoglucosylated precursor H10N1 high-mannose-type Nglycan that has been previously reported to be present in human blood serum [36]. In general, the average relative amounts of Endo H-released N-glycans of undifferentiated and adipogenically differentiated MSCs (5 or 15 days) were more different than those of 5 and 15 days adipogenically differentiated MSCs ( Fig.…”
Section: N-glycome Of Mscs and Its Changes During Adipogenic Differensupporting
confidence: 61%
“…The changes in relative amount of neutral hybrid-type N-glycans H5N2 (m/z 1579.7) and H6N2 (m/z 1783.8) in 15 days adipogenically differentiated MSCs and undifferentiated MSCs were statistically significant. In addition, a glycan of the composition H10N1 was detected in trace amounts at m/z 2355.1, which was verified as the monoglucosylated precursor H10N1 high-mannose-type Nglycan that has been previously reported to be present in human blood serum [36]. In general, the average relative amounts of Endo H-released N-glycans of undifferentiated and adipogenically differentiated MSCs (5 or 15 days) were more different than those of 5 and 15 days adipogenically differentiated MSCs ( Fig.…”
Section: N-glycome Of Mscs and Its Changes During Adipogenic Differensupporting
confidence: 61%
“…Aberrant glycosylation happens on several important serum glycoproteins, such as IgG, haptoglobin (Hp), and alpha-1-acid glycoprotein (AGP) in RA patients [2426]. Previous studies investigated the N-glycan patterns in the serum of RA patients [2729]. However, the comparison of glycans between RA patients and healthy controls in detail has not yet been investigated, since the isomeric glycans were difficult to be identified and annotated.…”
Section: Introductionmentioning
confidence: 99%
“…High‐mannose and hybrid‐type N‐ glycans with roles in immune response were released from human sera of rheumatoid arthritis patients (50 μL) with Endo‐H, separated from serum using C18‐cartridges (glycans in the flow‐through), fractionated on a high‐pH anion exchange column with pulsed amperometric detection, desalted and analyzed by MALDI‐TOF‐MS, or, labeled with APTS for CE‐LIF. The study found that high‐mannose structures Man 5–9 GlcNAc 1 were predominant, and one monoglucosylated structure Glc 1 Man 9 GlcNAc 1 and four hybrid structures were identified .…”
Section: The Analysis Of Glycoproteins By Other Techniques Than Msmentioning
confidence: 97%